Analysis of Wind Flow in Residential Areas of Johor Bahru City - Kubota, Tetsu; Ahmad, Supian (2005)
Most cities in Malaysia experience hot and humid climate during most part of the year. In large metropolitan cities such as Johor Bahru, the use of air conditioners to cool dwelling units has been increasing sharply partly due to continuing rise in disposable income brought about by recent high economic growth. This has resulted to significant rise in non-renewable energy consumption, thus does not contribute toward sustainability. Natural wind flow is one of the most effective energy-saving methods to improve the thermal environment at the neighborhood level. This paper presents the results of several wind tunnel tests on selected residential areas in Johor Bahru Metropolitan City. By comparing the average of wind velocity of each case studies, the paper discusses the planning methods at the residential neighborhood level area in order to create sufficient wind flow and help achieve energy saving and sustainability objectives in Malaysia.